TUAN GURU ZAINUDIN ABDUL MAJID’S EPISTEMOLOGICAL VIEWS ON INTEGRATION OF ISLAMIC EDUCATION IN LOMBOK, WEST NUSA TENGGARA - Fathurrahman Muhtar (IAIN Ponorogo, 2022)
AbstractCurrently, Muslims have a lack of understanding of epistemology, which results in the weak mastery of Muslim thought towards science and technology. In medieval times, Islamic thinkers with integrated thoughts were born from the mastery of epistemology sourced from the Qur'an and Sunnah.This study aims to explain Tuan Guru Kiai Zainuddin Abdul Majid's thinking in science development, making him a pioneer in Islamic education and a national hero in Lombok, West Nusa Tenggara. These paper methods are a historical approach and literature with content analysis. This study's results show that Tuan Guru Zainuddin Abdul Majid integrated his thoughts. His ideas are written in Tuhfatul Anfenaniyah Syarah Nahdlatuzzainiyah and his verse ya man yarum. His paper that religion and science are like buildings standing firmly. If religion and science are kept separate, so Muslims will fall behind. So, Islam people must comprehend Shari'a, Nahu, Shoref (grammar), Fiqh (Islamic law), astronomy, language, math, geometry, algebra, chemistry, and geography integrated to advance in this time and the future. His ideas were based on the scientific and dialectical foundations of Bayani, Burhani, and Irfani's epistemology, which is the basis for developing Islamic education. His thought was successful in developing Islamic education institutions based on Islamic integration. AbstrakLemahnya penguasaan epistemology menyebabkan lemahnya pemikiran umat Islam dalam penguasaan ilmu pengetahuan dan teknologi dewasa ini. Penguasaan epistemology yang bersumber dari al-Qur’an dan Sunnah telah melahirkan pemikir Islam yang memiliki pemikiran integral pada abad pertengahan. Penelitian ini bertujuan untuk menjelaskan pemikiran Tuan Guru Kiai Zainuddin Abdul Majid dalam pengembangan ilmu pengetahuan, yang menjadikannya sebagai pelopor pendidikan Islam dan pahlawan nasional di Lombok, Nusa Tenggara Barat. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan historis dan literatur dengan analisis konten. Hasil penelitian ini menunjukkan bahwa Tuan Guru Zainuddin Abdul Majid telah mengintegrasikan pemikirannya. Ide-idenya ditulis dalam Tuhfatul Anfenaniyah Syarah Nahdlatuzzainiyah dan syairnya ya man yarum. Dalam karya tulisnya diyatakan bahwa agama dan sains ibarat bangunan yang berdiri kokoh. Jika agama dan sains dipisahkan, maka umat Islam akan tertinggal. Baginya, umat Islam harus memahami Syariat, Nahu, Shoref (tata bahasa), Fiqh (hukum Islam), astronomi, bahasa, matematika, geometri, aljabar, kimia, dan geografi yang terintegrasi untuk mencapai kemajuan di masa ini dan masa depan. Ide-idenya didasarkan pada fondasi ilmiah dan dialektis epistemologi Bayani, Burhani, dan Irfani, yang dijadikan sebagai dasar dalam mengembangkan pendidikan Islam. Pemikirannya telah menghasilkan lembaga pendidikan Islam berbasis integrasi Islam